"An Ancient Celtic world had filled the air": the Celtic turn in Louis MacNeice's mid-century radio writing. Issue 3 (3rd July 2017) - Workman, Simon
Abstract: This article focuses on the specific meanings and figurations of Celtic identity, myth and history in three works by Louis MacNeice: his long poem Autumn Sequel (1954), written for broadcast on the BBC, and his two late radio plays They Met on Good Friday (1959) and The Mad Islands (1961). It will demonstrate that the poet moves from expressing an archaic and insipidly romanticised form of Celticity in Autumn Sequel, to depicting a significantly more sophisticated Celtic character and identity in They Met on Good Friday and The Mad Islands ; both dramas, it will be argued, are informed by a more thoroughly archipelagic conception of cultural formation and identity in the British and Irish isles. In all three texts, MacNeice's radiogenic engagement with Celtic material functions as a means of interrogating, though not always successfully, the forms and potentialities of human agency, community, and artistic activity within a post-war climate of political disenchantment, social fragmentation and perceived cultural vacuity. The essay will also demonstrate that MacNeice's Celtic themed radio writing is an important aspect of the poet's lifelong exploration of his psycho-cultural genealogy and a means of further clarifying his complex maternal and paternal inheritance.